2017
DOI: 10.1590/0100-3984.2016.0221
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound of ankles in the diagnosis of complications of chikungunya fever

Abstract: ObjectiveTo describe the main ultrasound findings of chikungunya fever in the ankle.Materials and MethodsThis was a cross-sectional observational study involving 52 patients referred to the Hospital Universitário Pedro Ernesto and presenting with clinical and biochemical evidence of chikungunya fever. The examinations were performed by a radiologist with more than 20 years of experience in ultrasound.ResultsThe predominant gender was female (in 88.5%), and the mean age was 58.4 years. The majority (61.5%) of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
15
2
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 38 publications
4
15
2
4
Order By: Relevance
“…A highpower Doppler signal (grade 2 or 3, Szkudlarek classification) was emitted by 28.3% of the effusions. Only 2 patients, one with unilateral and the other bilateral involvement, had detectable tenosynovitis, this is quite opposite to what is observed in the chronic phase of chikungunya (Canella, 2017;Mogami et al, 2017).…”
Section: Resultsmentioning
confidence: 61%
See 2 more Smart Citations
“…A highpower Doppler signal (grade 2 or 3, Szkudlarek classification) was emitted by 28.3% of the effusions. Only 2 patients, one with unilateral and the other bilateral involvement, had detectable tenosynovitis, this is quite opposite to what is observed in the chronic phase of chikungunya (Canella, 2017;Mogami et al, 2017).…”
Section: Resultsmentioning
confidence: 61%
“…Although the contribution of joint DUS to early rheumatoid arthritis diagnosis has been shown (Xiao et al, 2014), joint imaging studies on CHIKV-infected subjects are rare, except (Manimunda et al, 2010;Moga et al, 2018;Canella, 2017;Mogami et al, 2017). Joint DUS can confirm the presence of joint effusion, bone edema, synovial thickening, tenosynovitis and erosions in patients with persistent pain >1 month after the acute phase, but no ultrasound data are available for the early stage of the CHIKV disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our group recently performed studies in 50 patients with a confirmed diagnosis of chikungunya fever . The study was performed between 2016 and 2017 in Rio de Janeiro, Brazil.…”
mentioning
confidence: 99%
“…Classically, there are 3 phases of disease: acute (first 10 days), subacute (between 10 and 90 days), and chronic (after 90 days). In our studies , ultrasonography was performed, on average, during the subacute stage of the disease. We believe that this period is the most appropriate for identifying, with ultrasonography and power Doppler studies, cases with the potential to evolve poorly.…”
mentioning
confidence: 99%